Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Pada Pt Media Sempurna Nusantara Menerapkan Metode Copras - Siska, Siska (Jurnal Sains dan Teknologi Informasi, 2023)
Performance appraisal applies a measurement process in achieving predetermined goals. Performance appraisal can also be interpreted as a periodic determination of the operational effectiveness of an organization based on the vision and mission, organizational standards that have been previously determined. Organizations are basically operated on human resources so performance appraisal is actually apply assessment of human behavior in carrying out roles. The solution to the problem above is to build a Decision Support System to assist in determining employee performance assessments at PT Media Perfect Nusantara. The method chosen to support solving the problem above is the Copras method, namely by giving weight to each alternative option available. This research produces a Decision Support System that can recommend employee performance assessments at PT Media Perfect Nusantara using the Copras method. A trial was carried out by entering a data sample of 10 employee names. With the Decision Support System, it can provide recommendations for determining employee performance assessments based on rankings, employee performance assessments based on the largest ranking, namely: Alternative 9 (Lia Zannah) with a score of 100, Alternative 8 (Sinta Anggraini) with a score of 92.59 and Alternative 10 (Suratman ) with a value of 90.89